QuantityEr: An extensible and simple solution to obtain the amount of results of complex queries to GitHub - Soto Gómez, Ernesto (2020)
GitHub is a platform that provides hosting for software development version control using Git. It features an application programming interface to allow the software to interact with the platform. The enormous quantity of information Hosted in GitHub may be useful to make studies about the current presence of development tools in the open-source software development community. However, the search engine has restrictions that make it impossible to issue complex queries to the platform. In this report, it is described as an object-oriented and extensible solution, named QuantityEr, to obtain the number of search results of complex queries to GitHub by using the inclusion-exclusion principle. The mathematical definitions, as well as related concepts, are presented. The mathematical model is discussed. The application of general design and used development tools are presented. Also, the results of the execution examples are showed. It is concluded that the treated problem has been solved although more work may be done to improve the solution.